Why the Spanish State of autonomies could be the right example for the Bolivian State - Valentino M. C. M. Vondenhoff (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2009)
The study's aim is to analyze and investigate the characteristics of the regions demanding autonomy in Eastern Bolivia. Therefore the study takes a look at the Spanish political model, which could serve in a comparing and evaluating framework. The development of processes of autonomy has been part of Spanish history, especially in the regions of Catalonia and the Basque Country, which has contributed to the establishment of a stable democracy and a flourishing economy in Spain. Firstly, the study compares both autonomous regions in both countries out of a historical way. On the one hand, the reader will discover differences in the nationalist regions and on the other hand important similar developments in both countries. Finally, the study concludes that the Spanish State of Autonomies and its 1978 Constitution, established after Franco's death, could serve as the right example for the Bolivian State. Essential in the article is the search for a consensus over the different characteristics which exist between the two ideologies which are the main reason why the Bolivian State could be described as a weak State.
Keywords: 330